Oxyanion clusters with antielectrostatic hydrogen bonding (AEHB) in tetraalkylammonium hypodiphosphates. Issue 35 (15th August 2018) - Emami, Marzieh; Ślepokura, Katarzyna Anna; Trzebiatowska, Monika; Noshiranzadeh, Nader; Kinzhybalo, Vasyl
Abstract : Organic–inorganic salts of hypodiphosphoric acid with tetraalkylammonium cations have been synthesized and characterized by X-ray crystallography and IR spectroscopy. Abstract : Organic–inorganic salts of hypodiphosphoric acid with tetraalkylammonium cations have been synthesized and characterized by X-ray crystallography and IR spectroscopy. [(Et4 N)(H3 P2 O6 )]·0.5H4 P2 O6 ·2H2 O (1 ), [(Et4 N)2 (H2 P2 O6 )]·H4 P2 O6 (2 ), [( n -Bu4 N)(H3 P2 O6 )]·0.75H4 P2 O6 (3 ), [( n -Bu4 N)(H3 P2 O6 )]·0.25H4 P2 O6 ·0.53H2 O (4 ), [( n -Bu4 N)(H3 P2 O6 )]·0.25H4 P2 O6 (5 ) and [(Et4 N)Cl]·0.5H4 P2 O6 ·3H2 O (6 ) were obtained in the crystalline form. Their crystal structures reveal the formation of hydrogen-bonded networks (chains and layers) built from hypodiphosphate anions and acid molecules, assisted by water molecules in the hydrates. The networks are embedded in the tetraalkylammonium cations' framework. Free acid molecules are present in all of the studied substances. Compound5 was formed during a solid state dehydration reaction of4, which has taken place as single-crystal-to-single-crystal transformation. Water removal is associated with a symmetry increase and structure reconstruction, with the change in the conformation of one of the hypodiphosphate anions, from the usual staggered into a rarely occurring eclipsed conformation. In1, 3, 4 and5 the formation of clusters with antielectrostatic hydrogen bonding (AEHB) was observed.